Football Fitness – a new version of football? A concept for adult players in Danish football clubs. (August 2014) - Bennike, S.; Wikman, J. M.; Ottesen, L. S.
Abstract : This article explores a new Danish football‐based activity for health called Football Fitness (FF). Data are from quantitative and qualitative methods, and the theoretical framework for the analysis of the organizational form of FF is the theory of path dependency (Mahoney) and first‐ and second‐order change (Watzlawick et al.). Theories of Pestoff concerning differences between state, market, and the civil society and theories of voluntary associations in a Danish context (Kaspersen & Ottesen; Ibsen & Seippel) are applied. This article indicates how FF is a result of the changing landscape of sport and argues that it can be beneficial to target sports organizations and include the expertise of non‐profit sports clubs if the goal is to raise the physical activity level of the local community and make these long lasting. But the organizations need to consider how this is to be done. FF, established by the Danish Football Association (FA) and managed by the voluntary clubs, is one example in a Danish context. Data indicate that FF is beneficial to the clubs involved in a number of ways. Among other things, it attracts new user groups and improves the club environment, including social activities and parental environment.